State estimation for a class of nonlinear systems - Schwaller, Benoît; Ensminger, Denis; Dresp-Langley, Birgitta; Ragot, José (Zielona Góra: Uniwersytet Zielonogórski)
We propose a new type of Proportional Integral (PI) state observer for a class of nonlinear systems in continuous time which ensures an asymptotic stable convergence of the state estimates. Approximations of non-linearity are not necessary to obtain such results, but the functions must be, at least locally, of the Lipschitz type. The obtained state variables are exact and robust against noise. Naslin`s damping criterion permits synthesizing gains in an algebraically simple and efficient way. Both the speed and damping of the observer response are controlled in this way. Model simulations based on a Sprott strange attractor are discussed as an example.
Keywords: non-linear system; state observers; continuous time